Perbedaan Pewarnaan Rhoeo discolor pada Aquadest dan NaCl - Adita Dwi Arnas; Alvina Setya Dwitama; Diana Novita Sari; Najwa Wanda Hamidah; Salvin Dwi Putra Dundu Huki; Sovia Meldalina; Liss Dyah Dewi Arini (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2026)
This study aims to determine the changes occurring in the epidermal cells of Rhoeo discolor before and after plasmolysis and to analyze the factors influencing the occurrence of plasmolysis. Observations were conducted by applying water and NaCl solution to the leaf epidermal cells. The results showed that cells treated with water became swollen, with tightly arranged purple-colored cells, whereas cells treated with NaCl solution underwent plasmolysis, characterized by cell shrinkage due to the loss of turgor pressure. This condition occurred because the hypertonic environment caused water to move out of the cells. In addition, this study analyzed the relationship between the transpiration rate and the number of stomata through observations of the lower leaf epidermis. The analysis revealed a relationship between the transpiration rate and the number of stomata in Rhoeo discolor, which was influenced by environmental conditions such as dry, shaded, and humid environments. Therefore, Rhoeo discolor exhibits physiological and anatomical adaptations to its environment, making it potentially useful as a learning resource and as an ornamental plant that can be cultivated under various environmental conditions.